2014
DOI: 10.1093/ajh/hpu159
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Blood Pressure to Height Ratio Improves Accuracy for Hypertension in Childhood

Abstract: The modified BP:eHT13 ratio showed better sensitivity and specificity for the screening of BP abnormalities in children aged 5-12 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
22
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 19 publications
2
22
0
Order By: Relevance
“…However, the sensitivity and area under the curve (AUC) were lower in children aged 6 to 11 years than those in older children. Some researchers hypothesized that limitation was associated with the different growth rates of height and BP in young children . Using data from the Chinese National Survey on Students' Constitution and Health (CNSSCH), we observed that BPHR markedly declined with increasing age from 7 to 11 years and remained stable between 12 and 17 years .…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…However, the sensitivity and area under the curve (AUC) were lower in children aged 6 to 11 years than those in older children. Some researchers hypothesized that limitation was associated with the different growth rates of height and BP in young children . Using data from the Chinese National Survey on Students' Constitution and Health (CNSSCH), we observed that BPHR markedly declined with increasing age from 7 to 11 years and remained stable between 12 and 17 years .…”
mentioning
confidence: 86%
“…Mourato and colleagues recently proposed a modified formula for calculating BPHR (BP:eHT13) and found that BP:eHT13 was better than BPHR for screening elevated BP in Brazilian children (5–12 years). Therefore, it would be interesting to explore whether BP:eHT13 could improve the ability to identify elevated BP in Chinese children.…”
mentioning
confidence: 99%
“…The BP-to-height ratio (BPHT) is a simple screening tool that has shown good ability to identify high BP in children. 2 Conversely, variations in this formula, including the modified BP-to-height ratio (MBPHT) 3 and the new modified BP-to-height ratio (NMBPHT), 4,5 have been reported to provide better screening performance than the original BP-to-height ratio. However, a recent guideline changed the BP percentiles values in children and adolescents, 6 virtually nullifying these findings.…”
Section: New Modifications Of the Blood Pressure-to-height Ratio For mentioning
confidence: 99%
“…The first population (n = 2936; 1241 girls) was obtained from a database built from medical charts in a pediatric cardiology center in Brazil. 3 The second population (n = 6541; 3298 girls) was obtained from data derived from the National Health and Nutrition Examination Survey (NHANES) 1999-2014. [7][8][9] Only the first BP measurement was used in the analyses and details regarding the acquisition of data are reported elsewhere.…”
Section: New Modifications Of the Blood Pressure-to-height Ratio For mentioning
confidence: 99%
See 1 more Smart Citation